Celastrol suppresses growth and induces apoptosis of human hepatocellular carcinoma through the modulation of STAT3/JAK2 signaling cascade In Vitro and In Vivo - Rajendran, P.; Li, F.; Shanmugam, M.; Kannaiyan, R.; Goh, J.; Wong, K.; Wang, W.; Khin, E.; Tergaonkar, V.; Kumar, Alan Prem; Luk, J.; Sethi, G. (American Association for Cancer Research, 2012)
Cumulative evidences(s) have established that the constitutive activation of STAT3 plays a pivotal role in the proliferation, survival, metastasis, and angiogenesis and thus can contribute directly to the pathogenesis of hepatocellular carcinoma (HCC). Thus, novel agents that can inhibit STAT3 activation have potential for both prevention and treatment of HCCs. The effect of celastrol on STAT3 activation, associated protein kinases, STAT3-regulated gene products, cellular proliferation, and apoptosis was investigated. The in vivo effect of celastrol on the growth of human HCC xenograft tumors in athymic nu/nu mice was also examined. We observed that celastrol inhibited both constitutive and inducible STAT3 activation, and the suppression was mediated through the inhibition of activation of upstream kinases c-Src, as well as Janus-activated kinase-1 and -2. Vanadate treatment reversed the celastrol-induced modulation of STAT3, suggesting the involvement of a tyrosine phosphatase. The inhibition of STAT3 activation by celastrol led to the suppression of various gene products involved in proliferation, survival, and angiogenesis. Celastrol also inhibited the proliferation and induced apoptosis in HCC cells. Finally, when administered intraperitoneally, celastrol inhibited STAT3 activation in tumor tissues and the growth of human HCC xenograft tumors in athymic nu/nu mice without any side effects. Overall, our results suggest for the first time that celastrol exerts its antiproliferative and proapoptotic effects through suppression of STAT3 signaling in HCC both in vitro and in vivo.